Analysis of Military Court Decision Number 94-K/PM III-18/D/IX/ 2018 in The Case of Persecution Committed by Unscrupulous Military Personnel - Victor Januaris Berutu; Juanrico Alfaromona Sumarezs Titahelu; Elias Zadrach Leasa (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The decision of the Ambon Military Court III-18 Number: 94-K/PM III-18/AD/IX/2018 is a case of persecution. Basically, the decision of the Military Court is closed to members of the TNI itself so that public opinion never sees it. The decisions taken sometimes lack a sense of justice for members of the TNI who are accused. Therefore, the aspect of justice is one of the references in seeing the judge's consideration in making a Military Court decision. This research is to analyze and examine the military court verdict number 94-K/PM III-18/D/IX/2018 in the case of persecution committed by members of the TNI that has fulfilled a sense of justice and explain and examine the legal considerations of judges in imposing Military court verdict Number 94-K/PM III-18/D/IX/2018. This research uses normative research type. It was found that the Military Court Decision Number 94-K/PM III-18/D/IX/2018 in the case did not fully fulfill the sense of justice. The verdict only in terms of substantive justice is not fulfilled, while in terms of procedural justice it has been fulfilled. Thus the verdict has not fulfilled the sense of justice for the defendant himself. The judge's legal considerations in handing down Military Court Decision Number 94-K/PM III-18/D/IX/2018 in the case of persecution committed by members of the TNI are based on facts or events that occur and are supported by existing evidence, so that the judge can make decisions in accordance with the mistakes made